Předškolní vzdělávání v České republice pohledem pedagogického výzkumu. / Pre-primary education in the Czech Republic: a review of educational research - Veronika Najvarová; Zora Syslová (Czech Pedagogical Society, 2012)
The study brings an overview of empirical research carried out in the field of pre-primary education in the Czech Republic between the years 2000 and 2010. The authors analysed research papers published in research journals and relevant conference papers. The main aims of the review paper were to analyse the topics of the pre-primary school education research and to sum up the main findings. The review shows that the foci of realised research projects often lied on collecting data about pre-school children and their parents. Large proportion of the research also focused on undergraduate education of kindergarten teachers and their needs concerning inservice education. The research areas are however not covered systematically. The research projects are often isolated attempts to answer narrow research questions.Moreover, some of the analysed research projects show indications of weak (or poorly described) methodology. In the given period (2000-2010), there was a complete lack of large-scale research that would help bring deeper understanding of the processes within pre-primary education.